The role of makerspaces in advancing STEAM pedagogy: A systematic review - Tri Nurdiyanso; Hari Wahyono; Endang Sri Andayani (Inovasi Kurikulum, 2025)
The 21st century demands high-quality human resources equipped with critical, analytical, and creative thinking skills. In response to these needs, educational institutions have initiated and developed the Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning approach, which emphasizes interdisciplinary learning. In parallel, several schools have implemented makerspaces to support interdisciplinary learning. This study aims to systematically review the existing scholarly literature on the potential and challenges associated with implementing makerspaces in STEAM education. This study employs a literature review method, analyzing 13 Scopus-indexed articles published between 2014 and 2024, based on established inclusion criteria. The findings reveal that makerspaces function as constructivist learning environments that support learning through a STEAM-based approach. Furthermore, makerspaces are recognized for their potential to promote inclusive and equitable education by offering culturally relevant, student-centered opportunities that reflect the diversity of learners. However, several challenges remain, including limited access to tools and infrastructure, rigid curricular frameworks, insufficient teacher training, and the absence of assessment tools capable of capturing complex and multimodal learning outcomes. In conclusion, while makerspaces hold significant potential for enriching STEAM pedagogy, their successful integration relies heavily on systemic support, inclusive design practices, and continuous professional development for educators.   Abstrak Abad ke-21 membutuhkan sumber daya manusia yang berkualitas seperti keterampilan berpikir kritis, analitik, dan kreatif. Dalam memenuhi kebutuhan tersebut, lembaga pendidikan memulai dan mengembangkan pendekatan pembelajaran Science, Technology, Engineering, Arts, and Mathematics (STEAM), dimana fokus pembelajaran interdisplinary diutamakan. Di sisi lain, beberapa sekolah menerapkan makerspace dalam mendukung pembelajaran interdisplinary. Penelitian ini bertujuan untuk melakukan tinjauan sistematis terhadap potensi dan tantangan implementasi makerspace dalam pembelajaran STEAM berdasarkan literatur ilmiah. Metode penelitian ini menggunakan studi literatur review dengan menggunakan 13 artikel terindeks Scopus dan diterbitkan antara tahun 2014 hingga 2024, berdasarkan kriteria inklusi yang telah ditetapkan. Temuan menunjukkan bahwa makerspace berperan sebagai lingkungan belajar konstruktivis yang mendorong pembelajaran berbasis pendekatan STEAM. Selain itu, makerspace juga dinilai memiliki potensi untuk mendorong pembelajaran yang inklusif dan berkeadilan melalui penyediaan peluang yang relevan secara budaya dan berpusat pada siswa, sesuai dengan keragaman peserta didik. Namun demikian, terdapat tantangan seperti keterbatasan akses terhadap alat dan infrastruktur, kerangka kurikulum yang kaku, kurangnya pelatihan bagi pendidik, serta belum tersedianya alat asesmen yang mampu mengukur hasil belajar kompleks dan multimodal. Kesimpulannya adalah makerspace memiliki potensi besar dalam memperkaya pedagogi STEAM, keberhasilan integrasinya bergantung pada dukungan sistemik, praktik desain yang inklusif, dan pengembangan profesional yang berkelanjutan bagi pendidik. Kata Kunci: inovasi; kompetensi; makerspaces; pendidikan STEAM; tantangan